BATAKO DARI LIMBAH BOTOL PLASTIK : TINJAUAN KUAT TEKAN - Lailan Ni'mah; Isna Syauqiah; Agus Mirwan; Doni Rahmat Wicakso; Hesti Wijayanti (AL-ULUM: JURNAL SAINS DAN TEKNOLOGI, 2019)
This research was conducted with the aim of plastic bottle waste utilization in the manufacture of plastic bricks and to find out how much the compressive strength of plastic bricks produced. The variations used in this study are plastic bottle waste:glue = 1:1; plastic bottle waste:sand = 1:1 (without layer) and plastic bottle waste:sand = 1:1 (with 3 layers). From the test results show that the plastic brick with a variation of plastic bottle waste:glue = 1:1 has a compressive strength of 34980 N / mm2; plastic bottle waste:sand = 1:1 (without layer) has compressive strength of 18340 N / mm2 and plastic bottle waste:sand = 1:1 (with 3 layers) has compressive strength of 40750 N / mm2. Keywords: Waste Plastic Bottles, Plastic Bricks, Compressive Strength